1997
DOI: 10.1093/jac/40.suppl_1.83
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of grepafloxacin compared with other fluoroquinolones

Abstract: Preclinical investigations with grepafloxacin showed that its toxicological profile is similar to that of other fluoroquinolones. The photosensitizing effect of grepafloxacin was relatively weak and similar to that of ciprofloxacin. Grepafloxacin did not cause convulsions in mice when administered in conjunction with the non-steroidal anti-inflammatory drug fenbufen. Intravenous injection of grepafloxacin caused transient dysrhythmias in rabbits at a dosage of 10 mg/kg and ventricular tachycardia at 30 mg/kg i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…In patients receiving 600 mg/day, this side effect was reported in 26% of patients [50]. Overall, figures of 17% for taste perversion and 15% for nausea were reported for grepafloxacin in preregistration trials, and abnormal liver function tests were reported in up to 16% of patients given the drug in Japan [51,52].…”
Section: Individual Drugsmentioning
confidence: 97%
See 1 more Smart Citation
“…In patients receiving 600 mg/day, this side effect was reported in 26% of patients [50]. Overall, figures of 17% for taste perversion and 15% for nausea were reported for grepafloxacin in preregistration trials, and abnormal liver function tests were reported in up to 16% of patients given the drug in Japan [51,52].…”
Section: Individual Drugsmentioning
confidence: 97%
“…Although pseudomembranous colitis is certainly an unusual adverse event, it has been reported with quinolone use [23,24]. Taste perversion rates of 17% overall have been reported in patients treated with grepafloxacin [25].…”
Section: Systemsmentioning
confidence: 99%
“…Several investigators have rcporkd quinolones to be cytotoxic to eukaryotic cells. Preclinical toxicological evaluations have revealed nephrotoxicity and cardiotoxicity in laboratory animals to which fluoroquinolones were administered (23,26). Perhapb the most notable example of quinolone-associated cytotoxicity is chondrotoxicity-the ability of the class as a whole to induce arthropathy in juvenile animals ol' many species (1).…”
mentioning
confidence: 99%
“…Also, in animal experiments it exhibited a comparatively pronounced potential to induce dysrhythmia and ventricular tachycardia (Stahlmann and Schwabe 1997). Several studies have shown that grepa¯oxacin inhibits human ether-a-go-go-related gene (HERG) channels, which could explain its cardiotoxicity (Anderson et al 2001;Kang et al 2001).…”
Section: Fig 4a±dmentioning
confidence: 99%